Waste to Energy: Management of Biodegradable Healthcare Waste through Anaerobic Digestion - Dhakal, Nimesh; Karki, Amrit Kumar; Nakarmi, Mahesh (Nepal Journal of Science and Technology, 2016)
This research was carried out in 21m3 Technology for Economic Development (TED) model biogas plant constructed and operated at Bir Hospital, Kathmandu. The digester was fed with 95 kg of mixed waste per day in average generated at Bir Hospital. Average biogas production recorded per day was 5.78 m3 which increased to 8.09m3 per day after the feeding reached 15 tons after five months of regular feeding. The recorded burning time for this volume of gas was 12-14 hours per day in a stove of 0.22m3. Methane content in the gas reached up to 54% of the total volume and pH in the biodigester was maintained in a range of 6-7. The retention time of the biodigester was 147 days and the average energy content of biogas has been found as 4.38 Kwhth/m3. The payback period of the biodigester installed is 4 years when compared with LPG, since most of the hospitals use LPG as their cooking fuel it was only analyzed with the LPG. The total reduction of the GHGs was found to be 75.8 tons of CO2 equivalents per annum and the total reduction in terms of monetary benefits was 531.18 USD per annum. Except in one case the presence of E.coli was identified, beside its presence none of other harmful pathogens were detected in the slurry obtained. Nepal Journal of Science and Technology Vol. 16, No.1 (2015) pp. 41-48